A practical guide to early childhood curriculum - Eliason, Claudia Fuhriman, 1945-; Jenkins, Loa Thomson, 1942- (Boston : Pearson, 2012)
This volume is a guide to planning and implementing curriculum across the content areas, for children ages 3 to 8. It provides students with practical and highlighted strategies, unit and lesson plans, suggested activities, recipes, and more.
Includes bibliographical references and indexes.
Keywords: Education, Preschool -- Curricula; Early childhood education -- Curricula